2021
DOI: 10.1080/14670100.2020.1863701
|View full text |Cite
|
Sign up to set email alerts
|

Piloting the recording of electrode voltages (REVS) using surface electrodes as a test to identify cochlear implant electrode migration, extra-cochlear electrodes and basal electrodes causing discomfort

Abstract: Objectives: To determine if Electrode Voltage (EV) measurements are potentially suitable as a test for detecting extra-cochlear electrodes in cochlear implants (CIs) and to analyse voltages developed in different stimulation modes. Methods: EV measurements were made using surface electrodes in live mode without averaging in 17 adult cochlear implant (CI) users (18 ears). The effect of stimulation level, the position of the active recording electrode, repeatability and the position of the implant's active elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This has a very high maximum sampling rate, 400 kHz, enabling even individual CI pulses to be captured in detail. CI stimulation was as in the previous study (Grasmeder et al, 2021): CIs were stimulated in live mode from the Soundwave software. A level of 79 charge units was used for both threshold (T) and most comfortable (M) levels, for all electrodes except E8, which was stimulated at 120 units to provide a "marker electrode" that allowed identification of electrode number in the resulting traces.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…This has a very high maximum sampling rate, 400 kHz, enabling even individual CI pulses to be captured in detail. CI stimulation was as in the previous study (Grasmeder et al, 2021): CIs were stimulated in live mode from the Soundwave software. A level of 79 charge units was used for both threshold (T) and most comfortable (M) levels, for all electrodes except E8, which was stimulated at 120 units to provide a "marker electrode" that allowed identification of electrode number in the resulting traces.…”
Section: Figurementioning
confidence: 99%
“…Our previous study (Grasmeder et al, 2021) identified differences in EVs between fully inserted and partially inserted electrode arrays and for different recording electrode positions. This finding is consistent with the observation that EVs are nonuniform across the array even for normally functioning devices when one of the recording electrodes is positioned on the ipsilateral side to the implant (Eitutis et al, 2022).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Surface potentials measure electrical activity of the implant and are far larger than neural responses. More recently, Grasmeder applied a similar approach to detecting extra‐cochlear and migrating electrodes 10 . Here we present our clinical experience managing suspected Ultra V1 device faults detected using surface potentials.…”
Section: Introductionmentioning
confidence: 99%